STRATEGIES AND HOSPITAL ARRANGEMENTS: Study at a philanthropic hospital - Silveira Silva, Lara Jamille; Alex Castro Silva, Wendel (Revista Gestão & Saúde, 2018)
This study aimed to describe and analyze how philanthropic hospitals organize themselves in strategic terms, in the perception of managers who work in the hospital. A qualitative descriptive research was carried out, using the case study method. From the data collected, the following categories of analysis were defined: management model, organizational strategies, network architecture and hospital arrangements. The results show that, in terms of the management model, the hospital has a multiprofessional team, divided into management and administrative management. Regarding organizational strategies, maternal and child care was considered as a competitive differential of the hospital. It was observed that, among the several strategic indicators used, those linked to the care area are considered more important, since it makes it possible to evaluate the services provided by the institution. In relation to network architecture and hospital arrangements, it was identified that the institution establishes a partnership with only two agencies, the main reasons being: follow-up and monitoring of hospital management, exchange of experiences and discussion of indicators. The positive influence of the relationship networks on the financial economic performance of the hospital is emphasized, since they contribute to the production growth with more quality and humanization, revenue growth and cost reduction